Cognitive impairment after liver transplantation: residual hepatic encephalopathy or posttransplant encephalopathy? - Kornerup LS (Dove Medical Press, 2019)
Linda Skibsted Kornerup,1 Henning Pflugrad,2 Karin Weissenborn,2 Hendrik Vilstrup,1 Gitte Dam11Department of Hepatology and Gastroenterology, Aarhus University Hospital, Aarhus N, Denmark; 2Department of Neurology, Hannover Medical School, Hannover, GermanyAbstract: Liver transplantation (LT) represents the definitive treatment for end-stage liver disease. Cognitive impairment following LT is frequent, referred to as postliver transplant encephalopathy (PLTE). LT removes the underlying chronic liver disease, and until recently hepatic encephalopathy (HE) was assumed to be fully reversible after LT. However, increasing evidence indicates that some degree of cognitive impairment may be present after LT. To which extent PLTE reflects cognitive impairment caused by residual HE (RHE) or the combined effect of other factors affecting brain function before, during, and after LT is not clarified. None of the available psychometric and neurophysiological tests used for detecting HE is shown to be able to distinguish between etiologies. The available, mostly retrospective, clinical studies indicate a high prevalence of abnormal psychometric tests after LT, and not all seem to recover completely. The patients with earlier HE show the most marked improvements, suggesting that the clinical picture of the early PLTE, in fact, represents RHE. Other early post-LT etiologies for PLTE comprise cerebral ischemia, critical illness encephalopathy, and immunosuppressive therapy. Late-onset etiologies comprise diabetes and hypertension, among others. PLTE regardless of etiology is a worrying issue and needs more attention in the form of mechanistic research, development of diagnostic/discriminative tools, and standardized prospective clinical studies.Keywords: liver transplantation, hepatic encephalopathy, cirrhosis, cognitive impairment